(NsO^INENIQ(B: [1898-1903] /s (N~ASTX (B10s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B:s (NnAUKA(B,s, 1977)
(Nw (B10 (NTOM SOBRANIQ SO^INENIJ a(B.(Np(B. (N~EHOWA WO[LI RASSKAZY I POWESTI(B, (NNAPISANNYE (B1898-1903 (NGG(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs